Clinical and Radiological Characteristics of Acute Cerebrovascular Diseases Among Egyptian Patients With COVID-19 in Upper Egypt - Khedr, Eman M.; Soliman, Radwa K.; Abo-Elfetof, Noha; Amin, Mariam; Mansour, Ossama Yassin; Aly, Ahmed; Zaki, Ahmed F.; Saber, Mostafa (Frontiers in Neurology, 2021)
Abstract Background and Purpose: there is little information on the acute cerebrovascular complications of COVID-19 in Egypt. The aim of this study was to estimate the proportion of acute cerebrovascular disease (CVD) among COVID-19 patients and evaluate their clinical and radiological characteristics in comparison with non-COVID-19 CVD. Material and Methods: A retrospective study of cases of COVID-19 patients who presented with CVD in Assiut and Aswan University Hospitals was compared with cases of non-COVID-19 CVD in Qena University Hospital admitted prior to the pandemic. The following data were collected: clinical history and presentation, risk factors, comorbidities, brain imaging (MRI or CT), chest CT, and some laboratory investigations. Results: 55 (12.5%) of the 439 patients with COVID-19 had acute cerebrovascular disease. Of these, 42 (9.6%) had an ischemic stroke while 13 patients (2.9%) had hemorrhagic CVD. In the 250 cases of the non-covid-19 group; 180 had an ischemic stroke and 70 had a hemorrhagic stroke. A large proportion of patients with COVID-19 who presented with ischemic stroke had large vessel occlusion (LVO) which was significantly higher than in non-COVID-19 patients with CVD (40 % versus 7.2%, P < 0.001). Comorbidities were recorded in 44 (80%) cases. In COVID-19 ischemic stroke patients, risk factors (hypertension and IHD) and comorbidities (hepatic and renal) were significantly higher than in non-COVID patients. 23.5% had hemorrhagic CVD and six patients with LVO developed the hemorrhagic transformation. Conclusion: acute CVD among patients with COVID 19 was common in our study. LVO was the commonest. Hypertension, IHD, and anemia are the most common risk factors and could contribute to the worsening of clinical presentation. Comorbidities were common among patients with CVD although a large number had elevated liver enzymes and creatinine that were partially due to COVID-19 infection itself. The current results begin to characterize the spectrum of cerebrovascular disease associated with COVID-19 in patients in upper Egypt.